LIBRARY CAFE SEBAGAI SUATU TREN POPULER GENERASI Z - Puspita, Ika Destina; Endarwati, Endarwati; Rahayuningsih, Yanti (Program Studi Manajemen, 2025)
This study analyzes the popularity of the library cafe as a popular trend among Generation Z. The phenomenon is understood as a blend of literary culture and a modern lifestyle influenced by social media. Using a qualitative approach with a consumer needs theory framework, this research identifies the factors that drive Gen Z's preference for the place. The findings indicate that library cafes effectively fulfill four main needs of Gen Z: comfort, connectivity, aesthetics, and productivity. The need for comfort is met through a relaxed atmosphere and comfortable physical facilities. Connectivity, provided by strong Wi-Fi, transforms the space into a flexible